INTERCORRELATION OF THE SIZE OF THE EYE SLIT AND THE ANTHROPOMETRIC PARAMETERS OF THE ORGANISM - Madraximova N.R. (Scholar Express Journals, 2023)
Anthropometry is the science that defines physical measures of a person’s size, form, and functional capacities. Applied to occupational injury prevention, anthropometric measurements are used to study the interaction of workers with tasks, tools, machines, vehicles, and personal protective equipment — especially to determine the degree of protection against dangerous exposures, whether chronic or acute[1,15]. Existing data on the size and shape of industrial workers is limited. Because of the lack of anthropometric data for the general worker population, safety researchers have generally relied on data drawn from studies of military personnel, most of which was collected during the 1950s to 1970s. However, substantial anthropometric variability exists among the various U.S. workforce populations, and they are quite different from the average military population[11,12,13]. Industrial workers, such as the agriculture, truck driver, and firefighter workforces, are also anthropometrically very different from the average civilian population (Hsiao et al, 2002).
Keywords: Eye socket; skull; vision nerve